Familiar Face Priming: The Role of Second-Order Configuration and Individual Face Recognition Abilities. (February 2018) - Itz, Marlena L.; Schweinberger, Stefan R.; Kaufmann, Jürgen M.
The role of second-order configuration—that is, metric distances between individual features—for familiar face recognition has been the subject of debate. Recent reports suggest that better face recognition abilities coincide with a weaker reliance on shape information for face recognition. We examined contributions of second-order configuration to familiar face repetition priming by manipulating metric distances between facial features. S1 comprised familiar face primes as either: unaltered, with increased or decreased interocular distance, with increased or decreased distance between nose and mouth; or a different familiar face (unprimed). Participants performed a familiarity decision task on familiar and unfamiliar S2 targets, and completed a test battery consisting of three face identity processing tests. Accuracies, reaction times, and inverse efficiency scores were assessed for the priming experiment, and potential priming costs in inverse efficiency scores were correlated with test battery scores. Overall, priming was found, and priming effects were reduced only by primes with interocular distance distortions. Correlational data showed that better face recognition skills coincided with a weaker reliance on second-order configurations. Our findings (a) suggest an importance of interocular, but not mouth-to-nose, distances for familiar face recognition and (b) show that good face recognizers are less sensitive to second-order configuration.